2016
DOI: 10.1016/j.sdentj.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Measuring dental students’ preference: A comparison of light microscopy and virtual microscopy as teaching tools in oral histology and pathology

Abstract: Although light microscopy is the classical tool of teaching histology and pathology, virtual microscopy is a highly preferred substitute. We believe that virtual microscopy is a valuable teaching tool that enhances student educational experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 15 publications
0
14
0
11
Order By: Relevance
“…). Learners that performed better using VM in eight studies were notably all medical student learners (Krippendorf and Lough, ; Husmann et al, ; Anyanwu et al, ; Brueggeman et al, ; Helle et al, ; Diaz‐Perez et al, ; Tian et al, ; Alotaibi and ALQahtani, ). Improved performance using OM was reported in one of the studies (Helle et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…). Learners that performed better using VM in eight studies were notably all medical student learners (Krippendorf and Lough, ; Husmann et al, ; Anyanwu et al, ; Brueggeman et al, ; Helle et al, ; Diaz‐Perez et al, ; Tian et al, ; Alotaibi and ALQahtani, ). Improved performance using OM was reported in one of the studies (Helle et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, three studies surveyed resident learners: two of these studies reported OM as the preferred slide‐viewing modality (Koch et al, ; Donnelly et al, ) and one reported no preference (Brick et al, ). Medical student learners surveyed in five studies, reported VM as a favored learning modality (Mills et al, ; Anyanwu et al, ; McCready and Jham, ; Tian et al, ; Alotaibi and ALQahtani, ). Preference for a hybrid model was indicated in two studies that surveyed medical student learners (Neel et al, ; Braun and Kearns, ).…”
Section: Resultsmentioning
confidence: 99%
“…Second, the alumni accepted e-learning strategies as part of their curricula, and many reports identified several benefits after its implementation (27,28,30,(32)(33)(34)(35)(36)(37)(39)(40)(41)(42)(43)(45)(46)(47)(52)(53)(54)(55)(56)(57). Third, e-learning represents a point of debate within academics since some disciplines consider its application as valuable as the traditional teaching methods, while others considered it only as a good complement (29,42,44,50,53,58). Finally, despite the data available about e-learning in dentistry, many authors considered that more evidence is needed to understand the real impact and the best alternatives for its implementation (31,38,43,44,49,51).…”
Section: Maresca C Etal 2014 (58)mentioning
confidence: 99%
“…19 By presenting high-quality histology in a remotely accessible and easy-to-use format, the nonessential tasks of the learning event are minimised, in stark contrast to traditional methods of histology teaching such as light microscopy or static images which present significant physical and psychological barriers to effective education. 20 Virtual histology images were annotated in keeping with the Multimedia Learning Theory principles; 21 annotations automatically directed users to the relevant area of the image, at a magnification that best depicted the structure or process that was annotated. This acknowledges the limited capacity an individual has to process visual information.…”
Section: Additional Pedagogical Underpinningsmentioning
confidence: 99%